2011
DOI: 10.1111/j.1540-6229.2011.00316.x
|View full text |Cite
|
Sign up to set email alerts
|

A Regime‐Switching Approach to Modeling Rental Prices of U.K. Real Estate Sectors

Abstract: This article uses regime‐switching models of the threshold type to analyze the adjustment process of rental prices for three U.K. commercial real estate sectors over the period 1974–2008. The nonlinear models outperform their linear counterparts in in‐sample fit. Their out‐of‐sample forecasting ability is better whenever the corresponding linear models contain a significant amount of neglected nonlinearity. Regime switches are triggered when the growth rates of rental price exceed certain threshold levels. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Similarly, Harrami and Paulsson (2017) investigated rent modelling for the Swedish office market and found that the GDP was useful in predicting the direction of the real-estate market. Similar studies in the UK and the USA (Füss, Stein & Zietz, 2012;Tsolacos, 2006;Frankel & Saravelos, 2012;Buehler & Almeida, 2016) report that, in order to create predictive models, identifying the "right" set of variables that combine to trigger changes in the market was the first step. In particular, Buehler and Almeida (2016), noted that the risk of downturns in the commercial real-estate prices in USA cities was attributable to several macroeconomic indicators, including inflation rates, bond yields, consumer confidence, and employment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Harrami and Paulsson (2017) investigated rent modelling for the Swedish office market and found that the GDP was useful in predicting the direction of the real-estate market. Similar studies in the UK and the USA (Füss, Stein & Zietz, 2012;Tsolacos, 2006;Frankel & Saravelos, 2012;Buehler & Almeida, 2016) report that, in order to create predictive models, identifying the "right" set of variables that combine to trigger changes in the market was the first step. In particular, Buehler and Almeida (2016), noted that the risk of downturns in the commercial real-estate prices in USA cities was attributable to several macroeconomic indicators, including inflation rates, bond yields, consumer confidence, and employment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because the two purchasing groups are under different conditions and presumably hold different goals for the property, it would be expected that the models would differ to some degree. This difference could hold a particular significance in light of some models using rents instead of effective property values (16,17,19). In addition, the number of observations for some models was particularly low.…”
Section: Conclusion and Future Considerationsmentioning
confidence: 98%
“…As the market moves from one period to another, a regime switch occurs that changes the equilibrium natural occupancy in that market. This technique has been applied in London apartments and U.K. office, retail, and industrial real estate markets (Farrelly & Sanderson, 2005; Füss, Stein, & Zietz, 2011). More recently, regime switching has been applied to long-run valuation in the Paris office market (Bruneau & Cherfouh, 2015).…”
Section: Natural Occupancy Estimation: Constant and Varyingmentioning
confidence: 99%